The rise and fall of arbuscular mycorrhizal fungal diversity during ecosystem retrogression - Krüger, M.; Teste, F.; Laliberté, E.; Lambers, H.; Coghlan, M.; Zemunik, G.; Bunce, Michael (2015)
Ecosystem retrogression following long-term pedogenesis is attributed to phosphorus (P) limitation of primary productivity. Arbuscular mycorrhizal fungi (AMF) enhance P acquisition for most terrestrial plants, but it has been suggested that this strategy becomes less effective in strongly weathered soils with extremely low P availability. Using next generation sequencing of the large subunit ribosomal RNA gene in roots and soil, we compared the composition and diversity of AMF communities in three contrasting stages of a retrogressive >2-million-year dune chronosequence in a global biodiversity hotspot. This chronosequence shows a ~60-fold decline in total soil P concentration, with the oldest stage representing some of the most severely P-impoverished soils found in any terrestrial ecosystem. The richness of AMF operational taxonomic units was low on young (1000's of years), moderately P-rich soils, greatest on relatively old (~120 000 years) low-P soils, and low again on the oldest (>2 000 000 years) soils that were lowest in P availability. A similar decline in AMF phylogenetic diversity on the oldest soils occurred, despite invariant host plant diversity and only small declines in host cover along the chronosequence. Differences in AMF community composition were greatest between the youngest and the two oldest soils, and this was best explained by differences in soil P concentrations. Our results point to a threshold in soil P availability during ecosystem regression below which AMF diversity declines, suggesting environmental filtering of AMF insufficiently adapted to extremely low P availability.